Game understanding in international level soccer players - Luhtanen, P.; Heliskoski, J.; Häyrinen, M.; Vänttinen, T. (2000)
The purpose of this study was to examine game understanding in Finnish international level male (M) and female (F) soccer players both in U-16 and U-21 age groups. The number of participants in each group were as follows: M-16 (n=17), M-21 (n=17), F-16 (n=17) and F-21 (n=16). A test battery was constructed to measure game understanding in soccer. The test included 75 video segments of selected soccer matches showing offensive and defensive moves. The subjects had to orient themselves in the situations and then to try to understand play situations (space, time, speed and direction of the movements of the players and the ball). Each video segment began with 5-10 seconds of lead-up to the match situation to be evaluated. This was followed by 10 seconds of video of the last field of view of the video segment, upon which arrows representing three optional play, pass, or movement responses were imposed. Video segments were separated by 20 seconds of blank tape. This provided, in each video segment, an opportunity for the participants to select on a sheet of paper, which of the three options they believed to be best. Also, they had to choose one argument from a set of 8-10 written arguments, as to why they believed their chosen option was correct. For content validation and grading of the game understanding test, a group of youth national team coaches with two expert researchers graded the priority order of the options (2, 1, 0 point) and the arguments (2, 1, 0 point). Each player received scores related to the observed video vignettes as follows: the first was the number of the best selected options (SEO), the second score was the sum of the points obtained from the best selected argument options (ARO), the third was total amount of points TAP (maximum score 300 points). A 2-way ANOVA indicated that only the main effects of age were statistically significant in SEO F(1,67)=4.67, p=.034 , in ARO F(1,67)=15.71, p<.001 and in TAP F(1,67)=13.82, p<.001. No significant interaction between age and gender was found. The highest scores were reached by M-21 in SEO (113.7+7.0), ARO (85.4+8.1) and TAP (199.1+13.7). It can be concluded that males and females were equal in game understanding of soccer when video test was used. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)